Urine Osmolality and Renal Outcome in Patients with Chronic Kidney Disease: Results from the KNOW-CKD - Mi Jung Lee; Tae Ik Chang; Joongyub Lee; Yeong Hoon Kim; Kook-Hwan Oh; Sung Woo Lee; Soo Wan Kim; Jung Tak Park; Tae-Hyun Yoo; Shin-Wook Kang; Kyu Hun Choi; Curie Ahn; et al. (Karger Publishers, 2019)
Background: Urine osmolality indicates the ability of the kidney to concentrate the urine and reflects the antidiuretic action of vasopressin. However, results about the association between urine osmolality and adverse renal outcomes in chronic kidney disease (CKD) are conflicting. We investigated the association between urine osmolality and adverse renal outcomes in a nationwide prospective CKD cohort. Methods: A total of 1,999 CKD patients were categorized into 3 groups according to their urine osmolality tertiles. Primary outcome was a composite of 50% decline in the estimated glomerular filtration rate (eGFR), initiation of dialysis, or kidney transplantation. Results: During a mean follow-up of 35.2 ± 19.0 months, primary outcome occurred in 432 (21.6%) patients; 240 (36.4%), 162 (24.3%), and 30 (4.5%) in the lowest, middle, and highest tertiles, respectively. Low urine osmolality was independently associated with a greater risk of CKD progression (hazard ratio [HR], 1.71; 95% confidence interval [CI], 1.12-2.59). This association was particularly evident in patients with CKD stages 3-4 (per 10 mosm/kg decrease; HR, 1.02; 95% CI, 1.00-1.03). Adding urine osmolality to a base model with conventional factors significantly increased the ability to predict CKD progression (C-statistics, 0.86; integrated discrimination improvement [IDI], 0.021; both p < 0.001). However, adding both urine osmolality and eGFR did not further improve the predictive ability compared with the addition of eGFR only (C-statistics, p = 0.29; IDI, p = 0.09). Conclusions: Low urine osmolality was an independent risk factor for adverse renal outcomes in CKD patients, but its predictive ability did not surpass eGFR. Thus, kidney function should be considered while interpreting the clinical significance of urine osmolality.